Purification, Characterization, and Gene Expression of Rice Endo-β-N-Acetylglucosaminidase, Endo-Os - Maeda, Megumi; Okamoto, Naoko; Araki, Norie; Kimura, Yoshinobu (Frontiers in Plant Science, 2021)
In the endoplasmic reticulum-associated degradation system of plant and animal cells, high-mannose type free N-glycans (HMT-FNGs) are produced from misfolded glycoproteins prior to proteasomal degradation, and two enzymes, cytosolic peptide:N-glycanase (cPNGase) and endo-β-N-acetylglucosaminidase (endo-β-GlcNAc-ase), are involved in the deglycosylation. Although the physiological functions of these FNGs in plant growth and development remain to be elucidated, detailed characterization of cPNGase and endo-β-GlcNAc-ase is required. In our previous work, we described the purification, characterization, and subcellular distribution of some plant endo-β-GlcNAc-ases and preliminarily reported the gene information of rice endo-β-GlcNAc-ase (Endo-Os). Furthermore, we analyzed the changes in gene expression of endo-β-GlcNAc-ase during tomato fruit maturation and constructed a mutant line of Arabidopsis thaliana, in which the two endo-β-GlcNAc-ase genes were knocked-out based on the Endo-Os gene. In this report, we describe the purification, characterization, amino acid sequence, and gene cloning of Endo-Os in detail. Purified Endo-Os, with an optimal pH of 6.5, showed high activity for high-mannose type N-glycans bearing the Mana1-2Mana1-3Mana1 unit; this substrate specificity was almost the same as that of other plant endo-β-GlcNAc-ases, suggesting that Endo-Os plays a critical role in the production of HTM-FNGs in the cytosol. Electrospray ionization-mass spectrometry analysis of the tryptic peptides revealed 17 internal amino acid sequences, including the C terminus; the N-terminal sequence could not be identified due to chemical modification. These internal amino acid sequences were consistent with the amino acid sequence (UniProt ID: Q5W6R1) deduced from the Oryza sativa cDNA clone AK112067 (gene ID: Os05g0346500). Recombinant Endo-Os expressed in Escherichia coli using cDNA showed the same enzymatic properties as those of native Endo-Os.